If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -75 = -3x + 3 Reorder the terms: -75 = 3 + -3x Solving -75 = 3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -75 + 3x = 3 + -3x + 3x Combine like terms: -3x + 3x = 0 -75 + 3x = 3 + 0 -75 + 3x = 3 Add '75' to each side of the equation. -75 + 75 + 3x = 3 + 75 Combine like terms: -75 + 75 = 0 0 + 3x = 3 + 75 3x = 3 + 75 Combine like terms: 3 + 75 = 78 3x = 78 Divide each side by '3'. x = 26 Simplifying x = 26
| 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= | | -(4xy-10)+3(3xy+6)= | | 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 | | 18=3(v-13)-6 | | 5x+19+7x+98=213 | | 3t-8=-2the+7 | | 3t-8=-3 | | 5+4x=-1x | | 9h=-8+10h | | 8x-4=y | | 3(x+2)+23= | | 3x+7x-5x= | | 2(y-3)+5=3(x-1) | | 6(-5x+1)=-204 |